Procedimiento para atender en un determinado momento una auditoría forense en la cooperativa de ahorro y crédito San Miguel - coofisam - Cabezas Molina, Jury Alejandra; Motta Molina, Laura María (Universidad Antonio Nariño, 2022)
The purpose of this research was to determine the procedure to perform a forensic audit in the cooperative sector, especially in the savings and credit cooperatives. The proposal was carried out at Cooperativa de Ahorro y Crédito San Miguel Coofisam. For this purpose, a descriptive and documentary qualitative research was carried out, using the case study as a study method. The study was carried out through research in primary and secondary sources to diagnose the current internal control situation of Cooperativa de Ahorro y Crédito San Miguel - Coofisam. Next, the facts that could generate fraud in the entity were identified. These previous objectives were built thanks to the collection of information through the application of an instrument, which is considered of great importance in qualitative research, such as the interview, especially to managers and/or area managers of the case study company. The results allowed to propose a procedure to attend a Forensic Audit at Cooperativa de Ahorro y Crédito San Miguel - COOFISAM at a certain moment to be forewarned and organized for the operation of this important tool for the organizations.